FOOD AND BEVERAGE MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE: AN INVESTMENT ANALYSIS (IDX) - Diyan Riski Wijiutami; Sitti Retno Faridatussalam (SEAN Institute, 2023)
The development of the manufacturing industry in Indonesia has accelerated annually. The food and beverage industry is a subsector that continues to expand. This is a quantitative study using secondary data sources. For the period of 2017 to 2021, the data utilized pertains to the food and beverage subsector's listed manufacturers on the IDX. This study's population consisted of fifteen food and beverage sub-sector manufacturers listed on the Indonesia Stock Exchange. This research will employ the Multiple Linear Regression analysis approach, employing the test for the coefficient of determination, the simultaneous test, and the partial test. This study concludes that manufacturing enterprises in the food and beverage subsector on the IDX have, on average, a high degree of investment and profitability. To remain the customer's first choice, companies must continue to enhance product and service quality and monitor any possible threats.